2015
DOI: 10.1007/978-81-322-2337-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in Biogas Digester

Abstract: Biogas is a renewable energy source with different production pathways and various excellent opportunities to use. Biogas refers to a gas produced by anaerobic digestion (AD) or fermentation of organic matter including manure, sewage sludge, municipal solid waste, biodegradable waste, energy crops, or other biodegradable feedstock. Biogas is comprised primarily of methane and carbon dioxide. In this review, we discussed the worldwide status of biogas production, history of the biogas digester, classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Advantages: low cost, flexible (easy to move), and simple construction. Disadvantage: Low gas pressure may require gas pumps and scum cannot be removed during operation [15]. The design of the balloon digester plant is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages: low cost, flexible (easy to move), and simple construction. Disadvantage: Low gas pressure may require gas pumps and scum cannot be removed during operation [15]. The design of the balloon digester plant is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Limitations of this design include shorter lifespan, which does not exceed 2-5 years (Hoerz et al, 2008) and the anaerobic digestion in the system may be affected if leakage occurs. (Kumar et al, 2015).…”
Section: Balloon Bio-digestermentioning
confidence: 99%
“…Floating-drum reactors are similar to the fixed-dome reactors in operation; the major difference with floating drum reactor is the floating drum on top of the reactor that separates gas production and collection (Shi, 2014). They aremade of mild steel and the reactor walls and bottom are made of bricks; the reactor has a moveable gas holder, cylindrical digestion chamber with the inlet and outlet pipes connected (Kumar et al, 2015). These types of reactors are easy to operate and the drum can provide gas at constant pressure.…”
Section: 1fixed-dome and Floating-drum Reactorsmentioning
confidence: 99%
“…About 200,000 of these modified reactors have been installed in China with volume ranges from 2.5 m 3 to 10 m 3 . Reinforced plastic reactors are developed for biogas production in order to make them weather or UV resistant (Kumar et al, 2015) thereby increasing their lifespan. Research has shown that methane content of biogas produced using reinforced plastics is 15.3% NmlCH4/gVS at 30 %TS after long acclimatization of the inoculum.…”
Section: 23latest Generation Plastic Reactorsmentioning
confidence: 99%